PENINGKATAN KUALITAS PEMBELAJARAN ANAK USIA DINI DI TK FATIMAH PALEMBANG - Baidha, Pratista Sara (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Early childhood education is the initial stage in forming a child's character and potential. The aim of this scientific journal is to analyze and describe efforts to improve the quality of early childhood learning at Fatimah Palembang Kindergarten. The research method used was observation and interviews with teachers at Fatimah Kindergarten in Palembang. The results of the research show that there are several factors that contribute to improving the quality of early childhood learning at Fatimah Palembang Kindergarten. First, the important role of teachers in providing innovative and fun learning approaches. Teachers need to apply interactive learning methods, such as role playing, stories, and playing while learning. Second, collaboration between teachers and parents is very important in improving the quality of early childhood learning. Parents need to be involved in their child's learning process at home and communicate regularly with teachers to monitor their child's development. Third, adequate learning facilities also contribute to improving the quality of learning. Fatimah Palembang Kindergarten needs to pay attention to adequate facilities, such as a safe and comfortable playroom, a complete library, and attractive learning equipment.